Fast Burst Synchronization for Power Line Communication Systems. (10th May 2007) - Bumiller Bumiller, Gerd Gerd; Lampe Lampe, Lutz Lutz
Abstract : Fast burst synchronization is an important requirement in asynchronous communication networks, where devices transmit short data packets in an unscheduled fashion. Such a synchronization is typically achieved by means of a preamble sent in front of the data packet. In this paper, we study fast burst synchronization for power line communication (PLC) systems operating below 500 kHz and transmitting data rates of up to about 500 kbps as it is typical in various PLC network applications. In particular, we are concerned with the receiver processing of the preamble signal and the actual design of preambles suitable for fast burst synchronization in such PLC systems. Our approach is comprehensive in that it takes into account the most distinctive characteristics of the power line channel, which are multipath propagation, highly varying path loss, and disturbance by impulse noise, as well as important practical constraints, especially the need for spectral shaping of the preamble signal and fast adjustment of the automatic gain control (AGC). In fact, we regard the explicit incorporation of these various requirements into the preamble design as the main contribution of this work. We devise an optimization criterion and a stochastic algorithm to search for suitable preamble sequences. A comprehensive performance comparison of a designed and two conventional preambles shows that the designed sequence is superior in terms of (a) fast burst synchronization in various transmission environments, (b) fast AGC adjustment, and (c) compliance of its spectrum with the spectral mask applied to the data transmit signal.